An Empirical Study of Affective Commitment: the Case of Machinery Enterprises in Hochiminh City - Dinh Nguyen, Hoa; My Thi Tran, Diem; Ba Vu, Thanh; Thuy Thi Le, Phuong (Organizations and Markets in Emerging Economies, 2020)
The study aims to investigate the impact of participation in decision-making (PDM) and perceived organizational support (POS) on affective commitment in machinery enterprises. The study applies structural equation modeling (SEM) to test the research hypotheses. The authors surveyed 220 employees who work in machinery enterprises to collect data for the research. The study results indicate that both PDM and POS positively impact affective commitment. The findings provide empirical evidence to support the theoretical models that PDM and POS have a positive effect on affective commitment. The findings have implications for management theory: PDM and POS are the key antecedents of affective commitment. The findings also have implications for practical management in the machinery enterprises that managers should practice both PDM and POS to increase affective commitment.